Molybdate-intercalated NiMn layered double hydroxide nanoarrays supercapacitor electrode with enhanced stability via a differentiated deposition strategy - Zeng, Lei; Tang, Tingfu; Liang, Yifan; Jiang, Shiwen; Xu, Xuetang; Wang, Fan (Journal of power sources, 2024)
Nickel-manganese layered double hydroxide (NiMn-LDH) is a promising electrode material for supercapacitor due to its unique two-dimensional (2D) layered structure, adjustable interlayer spacing, tailorable chemical valences, and ion exchange ability. However, NiMn-LDH still suffers from poor conductivity and low cyclic stability during the charge/discharge process. In this work, NiMn-LDH nanoarrays are grown on a carbon cloth substrate using a novel differentiated solvo/hydrothermal deposition strategy, in which molybdate anions act as precipitators during the second-step deposition and also as intercalated anions in the gallery of NiMn-LDH. The molybdate-intercalated NiMn-LDH nanoarray consists of open channels that allow electrolyte access and interconnected nanosheets decorated with tiny nanoflakes, and exhibits a high capacitance of 1712 F g−1 at 1 A g−1 with good cyclic performance, retaining 94.4 % of its capacitance after 8,000 charge/discharge cycles. The as-assembled NiMn-LDH//activated carbon hybrid supercapacitor delivers a high specific capacitance of 148.4 F g−1 at 1 A g−1, and achieves a high energy density of 66.8 Wh kg−1 at a power density of 900 W kg−1 with an excellent cycle stability (96.6 % capacitance maintained after 12,000 cycles). [Display omitted] •Molybdate as precipitator and intercalated anions for differentiated deposition.•NiMn-LDH nanoarray comprises open channels for effective electrolyte access.•Nanosheets decorated with tiny nanoflakes for enhanced accessible surface area.•Molybdate-intercalated NiMn-LDH shows the capacitance of 1712 F g−1 at 1 A g−1.•All-solid-state asymmetric supercapacitor delivers 66.8 Wh kg−1 at 900 W kg−1.